(untitled) (Research, Society and Development, 2020)
The purpose of this work is to evaluate the quality of spelt flour in different concentrations of Transglutaminase (TGase) for the production of natural fermentation breads of spelt flour is known as an ancestral grain which, despite its nutritional qualities, does not have a good protein quality for the production of long-fermented breads. Laboratory rheological tests were used for baking and analysis of bread volume and dough at different fermentation times (2 - 4 - 6 hours) with different TGase concentrations (0, 1000, 3000 and 5000 ppm). Design in the study: the tests were done with 3 repetitions. Data were collected on the volume and dough of the baked bread in addition to the rheological evaluations of the dough through alveography, extensography and alveography tests. The dough and volume of the baked loaves were analyzed through the ANOVA-two way test, including the interactions between the predictor variables and the rheological analyses wre analyzed through Tukey’s additivity test and Analysis of Variance. In the evaluation of the dough and volume of bread, it was found that in spelt flour the best concentration was 3000 in the fermentation time of 4 hours. In all TGase concentrations it was noticed an increase in spelt flour strength and an increase in elasticity, however, it did not reflect in the improvement in the dough extensibility capacity, concluding significant effect in spelt flour characteristics in all TGase concentrations.